KINERJA LALU LINTAS JALAN PROVINSI KM 18 KABUPATEN PENAJAM PASER UTARA - Irna Hendriyani; Hikmah Maya Sari (Display Architecture Journal, 2023)
The growth of traffic flow at Province road Km. 18 of District of Penajam Paser Utara is increasing in every year. The road is crowded path with type 4 lane and 2 ways with a median (4/2 D). The road is main road for residential streets, education area, worship area and government area and that in peak hours is crowded. The study use the Indonesia Highway Capacity Manual (MKJI,1997) for analysis the results. The analysis show degree of saturation (DS): 0,30. Travelling Speed (V) of Light vehicle (V): 44.05 with level service B. From the results of assuming the traffic 5 years, it is obtained traffic volume: 1488 cpu/hours, the degree of saturation: 0.32, the travel speed of light vehicles: 44,05. The high volume of vehicle and the rate of barriers side contribute to the significant influence on the traffic performance along the Province Road Km. 18 of Penajam Paser Utara District. The alternative effective way is to reduce the side barrier. This way reduce effectively the value of degree of saturation to 0,29. The speed of light vehicles is 48.51 km /hours. The side barrier is low (L): 237 events.